2018
DOI: 10.1007/s12298-018-0550-3
|View full text |Cite
|
Sign up to set email alerts
|

Impact of maturity on phenolic composition and antioxidant activity of medicinally important leaves of Ficus carica L.

Abstract: L. is one of the oldest trees belonging to the mulberry family. It has both nutritional and medicinal benefits, as it is a source of potential bioactive compounds. Fig leaves were collected at four maturation stages, to evaluate the variation in polyphenolic compounds, antioxidant activity, and different pigments level. Polyphenols were identified using HPLC-DAD. Different pigments level, total phenolic contents, and radical scavenging activity were quantified. The HPLC analysis revealed the presence of fourte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 36 publications
3
14
0
3
Order By: Relevance
“…Phenolic and flavonoids are low molecular weight compounds playing vital role in plant physiology and development . In the present study, SA considerably stimulated phenolic and flavonoids biosynthesis in cell cultures of flax.…”
Section: Resultssupporting
confidence: 51%
“…Phenolic and flavonoids are low molecular weight compounds playing vital role in plant physiology and development . In the present study, SA considerably stimulated phenolic and flavonoids biosynthesis in cell cultures of flax.…”
Section: Resultssupporting
confidence: 51%
“…The plant contains natural compounds, including minerals, vitamins, amino acids, fibers, phytosterols, and also phytochemicals, such as phenolic acids, flavonoids, isoflavonoids, anthocyanins, triterpenoids, sesquiterpenes, coumarins, lignans, and alkaloids with potential antioxidant activities . The major reported phytoconstituents of F. carica are ferulic acid, psoralen, bergapten, pyrogallic, 3–5‐dimethoxyphenol, coumaric acid, cinnamic acid, quercetin, luteolin, biochanin‐A, apigenin rutinoside, kaempferol, and ficusogenin in leaves; cyanidin‐3‐glucoside, cyanidin‐3‐ O ‐rhamnoglucoside, (epi)catechin, pelargonidin 3‐glucoside, pelargonidin 3‐rutinoside, peonidin 3‐rutinoside, umbelliferone, scopoletin, stilbenes, and quinines in fruits; psoralen and β ‐sitosterol in roots; lanosterol, lupeol acetate, β ‐amyrin, β ‐sisterol, pentanal, hexanal, heptanal, benzaldehyde, octanal, 7‐6‐methyl‐5‐hepten‐2‐one, monopterpenes, α ‐thujene, α ‐pinene, β ‐pinene, limonene, terpinolene, 6‐ O ‐Linoleyl‐ β ‐ d ‐glucosyl‐ β ‐sitosterol, 6‐ O ‐Oleyl‐ β ‐ d ‐glucosyl‐ β ‐sitosterol, 6‐ O ‐palmitoyl‐ β ‐ d ‐glucosyl‐ β ‐sitosterol, and ficin in latex . Different parts of F. carica , alone or in combination with other plants, have been used as pharmacological agents in the treatment of different diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Different parts of F. carica , alone or in combination with other plants, have been used as pharmacological agents in the treatment of different diseases. Several studies have indicated the use of fig as antioxidant and sunscreen and also for its anti‐inflammatory, anti‐helminthic, anticarcinogenic, anti‐tumor, antifungal, antimalarial, antiseptic, cytotoxic, antimutagenic, antipyretic, antispasmodic, antidiabetic, hypolipidemic, diuretic, expectorant, hepatoprotective, immunomodulator, erythropoietic effects as well as its use to manage anemia . The concentration of secondary metabolites, especially flavonoids and anthocyanins, and the color of fig fruit, is dependent on the fig cultivars and genotypes .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations